Ecotourism Visit Intentions: Linking Environment Identity, Nature Enjoyment and Social Media - Septiarini, Eka; Adialita, Tania (Indonesian Journal of Sustainability Accounting and Management, 2025)
This study examines how environmental identity and social media consumption influence individuals’ visit intention to ecotourism sites in West Java, with enjoyment of nature serving as a mediator. Data from 468 respondents were analyzed using structural equation modeling, and results indicate that both environmental identity and social media consumption have significant direct and indirect effects on visit intention via enjoyment of nature. The model demonstrates strong explanatory power, as evidenced by favorable fit indices. The study’s novelty lies in integrating environmental identity, social media consumption, and enjoyment of nature into a single framework—whereas most prior research treated these constructs in isolation—thereby revealing the synergistic interplay of cognitive, digital, and emotional experiences in shaping ecotourism motivations. These findings offer destination managers practical guidance for crafting marketing strategies that resonate both emotionally and ethically with young, digitally savvy travelers.